3D network porous polymeric composites with outstanding electromagnetic interference shielding. (23rd March 2016) - Wang, Hui; Zheng, Kang; Zhang, Xian; Ding, Xin; Zhang, Zhongxiang; Bao, Chao; Guo, Le; Chen, Lin; Tian, Xingyou
Abstract: A novel and highly efficient technique, combination of hot-pressing and selective etching, was proposed to manufacture porous nanocomposites based on poly(vinylidene fluoride) (PVDF) and multiwall carbon nanotubes (MWCNTs) with three-dimensional(3D) networks. Benefitting from the 3D conductive network, a dramatic change in electrical conductivity was observed from 10 −16  S cm −1 for pure PVDF to 1 S cm −1 for porous nanocomposites (at 15 wt% MWCNTs loading). In addition, the obtained porous composites achieved an electromagnetic interference (EMI) shielding effectiveness (SE) of approximately 56.72 dB with a density of 0.79 g cm −3 and a thickness of only 2 mm. The EMI shielding mechanisms of such porous materials were also discussed and it suggested that the dominant contribution to EMI SE was absorption rather than reflection in the X-band frequency region.